Acute myeloid leukemia with t(4;12)(q12;p13): A morphological dilemma - Umang V Patel; S R Arun; Deepak Kumar Mishra; Mayur Parihar (Wolters Kluwer Medknow Publications, 2016)
Cytogenetics has a pivotal role in risk stratification of acute myeloid leukemia (AML). We report a case of AML with a t(4;12)(q12;p13). To the best of our knowledge, there are about 24 cases of t(4;12) reported in AML which are usually misdiagnosed as lymphoproliferative disorders on morphological assessment. This case showed specific clinical, morphological, and immunophenotypic features such as (1) pseudo lymphoid morphology, (2) dysplasia in granulocytic series, (3) an immature immunophenotype with positivity for CD34 and CD117, and (4) poor treatment response.